Experimental investigation of aerofoil tonal noise generation. (25th May 2014) - Pröbsting, S.; Serpieri, J.; Scarano, F.
Abstract The present study investigates the mechanisms associated with tonal noise emission from a NACA 0012 aerofoil at moderate incidence (<alternatives><inline-graphic xlink:href="ark:/27927/pghjkz3b1j" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> <![CDATA[0^° , 1^° , 2^° ]]> </alternatives> and <alternatives><inline-graphic xlink:href="ark:/27927/pghjkz3954" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> <![CDATA[4^° ]]> </alternatives> angle of attack) and with Reynolds numbers ranging from 100 000 to 270 000. Simultaneous time-resolved particle image velocimetry (PIV) of the aeroacoustic source region near the trailing edge and acoustic measurements in the far field are performed in order to establish the correspondence between the flow structure and acoustic emissions. Results of these experiments are presented and analysed in view of past research for a number of selected cases. Characteristics of the acoustic emission and principal features of the average flow field agree with data presented in previous studies on the topic. Time-resolved analysis shows that downstream convecting vortical structures, resulting from growing shear layer instabilities, coherently pass the trailing edge at a frequency equal to that of the dominant tone. Therefore, the scattering of the vortical structures and their associated wall pressure fluctuations are identified as tone generating mechanisms for the cases investigated here. Moreover, wavelet analysis of the acoustic pressure and velocity signals near the trailing edge show a similar periodic amplitude modulation which is associated with multiple tonal peaks in the acoustic spectrum. Periodic amplitude modulation of the acoustic pressure and velocity fluctuations on the pressure side are also observed when transition is forced on the suction side, showing that pressure-side events alone can be the cause.